Leading Pedestrian Intervals at Urban Crosswalks: Effects on Safety for Travelers Who Are Blind. (January 2023) - Bourquin, Eugene A.; Bieder, Joy; Wall Emerson, Robert; Franck, Lukas
Introduction: The use of leading pedestrian intervals (LPIs) creates safer street crossings for typical pedestrians, giving them a head-start into the crosswalk. The LPI, however, delays the onset of the traditional traffic sound cue that pedestrians who are blind use to initiate crossing streets. LPIs can create situations where pedestrians who are blind will frequently begin or end crossings or both against the pedestrian signal.Methods: The researchers conducted two sets of observations in an urban environment. They measured the seconds from the initiation of the vehicular circular green signal to the front of the first vehicle passing through the center of the intersection (n = 40) to calculate the average driver's delay. Pedestrians who are blind, to confirm a straight-through surge of parallel traffic (i.e. not turning vehicles), listen for a vehicle to reach the roadway center to know it is the appropriate time to initiate a crossing. In the second set of observations (n = 40), the researchers recorded the length of the Walk, Flashing Don't Walk, and LPI to calculate average impacts on crossing.Results: The average time for vehicles to reach the center of the intersection was 6.0 s. When there was an LPI, on average the clearance for pedestrians after reaching the far corner was 0.49 s; for Walk intervals, there was an average of 3.35 s margin of time to begin crossing.Discussion: These observational studies verify the crossing latencies for pedestrians who are blind. At crosswalks with LPI, pedestrians can be expected to cross after the Walk sign has expired 15 to 38% of the time and end their crossing 40 to 82% of the time when the visual display says Don't Walk .Implications for Practitioners: Orientation and mobility specialists should instruct students on how to identify intersections with LPI to assist in decision making. Traffic management remediation is the installation of an accessible pedestrian signal (APS); specialists should advocate for the installation of APS where LPIs are implemented and teach students how to use APS.